Efficiency of the emissions trading scheme – a theoretical approach - Kudełko, Mariusz (Efektywność handlu uprawnieniami zbywalnymi – podejście teoretyczne, 2019)
The purpose of the article is to indicate the most important feature of the emissions trading system – efficiency – which was the basis for the proposed and currently implemented legal solutions for environmental protection actions. The main reasons for the discrepancies in environmental and economic policies are described. The most important of which are the unequal treatment of the own costs of energy companies and the external costs caused by the emissions of the main pollutants. This causes incorrect investment decisions (allocation) made by the energy producers. The conditions under which the emissions trading system fulfil the criterion of allocation and cost efficiency are given. The analysis of some features that are the essence of this instrument creates the premise for a better understanding of its operation. The negative opinions formulated, also in Poland, emerge mainly from the opinions about this instrument, focusing only on its negative impact on energy prices increases, but also the practice of the EU ETS, which is largely inconsistent with its original assumptions
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 79-89
Keywords: emission trading system; energy sector; allocation and cost efficiency; handel uprawnieniami zbywalnymi; efektywność alokacyjna i kosztowa; sektor energetyczny